2019
DOI: 10.30845/aijcr.v9n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory and Confirmatory Factor Analysis of Mental Health Recovery Knowledge Inventory

Abstract: The Recovery Knowledge Inventory is a self-report measure intended to identify the knowledge of and attitudes toward recovery-oriented care among mental health providers and staff. The developers of the Recovery Knowledge Inventory found good-to-poor reliability statistics on the original four-factor model. This study reassessed the psychometric properties of the Recovery Knowledge Inventory using exploratory factor analysis to find a factor structure that was a good fit for the model. Thus, a confirmatory fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…In our study, five out of seven items were loaded on Factor 1 (roles and responsibility) and all six items were loaded on Factor 2 (non-linearity of the recovery process), based on the original factor structure ( 4 ). These findings are consistent with several other studies that reported similar item loading on Factor 1 ( 21 , 24 , 26 ). Carvalho and Chima ( 24 ) found that taking a single factor structure and renaming Factor 1 as a ‘recovery process’ rather than ‘roles and responsibility’ was more inclusive of Recovery.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, five out of seven items were loaded on Factor 1 (roles and responsibility) and all six items were loaded on Factor 2 (non-linearity of the recovery process), based on the original factor structure ( 4 ). These findings are consistent with several other studies that reported similar item loading on Factor 1 ( 21 , 24 , 26 ). Carvalho and Chima ( 24 ) found that taking a single factor structure and renaming Factor 1 as a ‘recovery process’ rather than ‘roles and responsibility’ was more inclusive of Recovery.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with several other studies that reported similar item loading on Factor 1 ( 21 , 24 , 26 ). Carvalho and Chima ( 24 ) found that taking a single factor structure and renaming Factor 1 as a ‘recovery process’ rather than ‘roles and responsibility’ was more inclusive of Recovery. These two studies that used the method of exploring the factors and confirming it with CFA came out with a similar construct.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The maximum likelihood method was used to fit the structural equation model. This study refers to De Carvalho and Chima ( 2014 ) for the fitting indicators and the criteria for the goodness of fitting indicators, as detailed in Table 2 . All fitting indicators of the mediation model are within the acceptable range, indicating that the model fits well.…”
Section: Resultsmentioning
confidence: 99%
“…Second, we used Amos 24.0 to test the mediation model of work addiction in the relationship between role overload and missed nursing care by constructing a structural equation model (SEM). This study refers to De Carvalho and Chima ( 2014 ) for the fitting indicators and the criteria for the goodness of fitting indicators, as detailed in Table 2 . And we also used Amos 24.0 to test the moderating mediation model through path analysis.…”
Section: Methodsmentioning
confidence: 99%